PERSEPSI SISWA TERHADAP EFEKTIVITAS APLIKASI PRESENSI DIGITAL “SREGEP” DALAM MENINGKATKAN KEDISIPLINAN SISWA KELAS VIIID DI MTS NEGERI 1 YOGYAKARTA - Ikha Ayu Sulistyarini; Jumintono Jumintono; Saryanto Saryanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Student attendance is a fundamental indicator of learning success, influenced by both internal and external factors. In line with technological advancement, MTs Negeri 1 Yogyakarta developed a barcode-based digital attendance application called